It Happens in the Cities and All Over Russia - Tovmasyan, Eduard (project baikal, 2017)
Basing on the materials of the research in the field of territorial planning and urban development, as well as on his personal research and design experience in territorial and urban planning within the so-called nonmetropolitan practice, the author of the article gives concrete examples of this practice and evaluates them.